Membangun Sistem Informasi Usaha Mikro Kecil dan Menengah (UMKM) Berbasis Web - Didi Susianto (Universitas Pahlawan Tuanku Tambusai, 2022)
Information systems for food-processed MSMEs must be built and start using computerized systems and online marketing. This method is expected to make it easier to find information about the profile of UMKM, superior products, and so on. Online marketing can encourage the entry of UMKM products more broadly. The purpose of this study is to produce an information system that can improve the economy of UMKM members in terms of product marketing and to produce an information system that can display UMKM products to the wider community, especially website users. and efficient so that the creation of data on SMEs in Negeri Katon District is not too late. In addition, the product marketing information system for the new UMKM in Negeri Katon Sub-district is easier in the process of ordering and paying for products at UMKM in Negeri Katon Sub-district. Keywords: UMKM Data Processing, Use Cases, Class Diagrams, Activity Diagrams